Professional Identity Formation in HIV Care: Development of Clinician Scholars in a Longitudinal, Mentored Training Program. Issue 3 (2018) - Carlberg-Racich, Suzanne; Wagner, Cornelia M. J.; Alabduljabbar, Salma A.; Rivero, Ricardo; Hasnain, Memoona; Sherer, Renslow; Linsk, Nathan L.
Abstract : Introduction: The Clinician Scholars Program is designed to improve the capacity and quality of HIV care by training clinicians in underserved areas. A mentoring approach is used to deliver individualized educational opportunities over the course of a year focused on preparing clinicians to provide high-quality patient-centered HIV care. Evaluation of the program has illustrated increases in knowledge, skills, and practice behavior, yet critical domains remain unexplored, particularly the potential for the program to affect professional identity formation and networking between individual clinicians. Methods: Qualitative exit interviews ( N = 50) were conducted over 4 years of the Clinician Scholars Program. Interviews were transcribed and analyzed using an open-coding process with multiple coders. Interrater reliability was assessed. Themes related to professional development and networking emerged. Results: Thematic analysis revealed changes in several professional development domains, including self-efficacy, HIV care clinician identity, and career development. In addition, clinicians began to develop key connections with mentors, other clinicians, and health systems—gaining a foundation in the HIV care community, enabled and strengthened by growth in professional confidence and competence within the clinician's care context. Discussion: Evaluations of clinical training programs often focus on knowledge and skill gains without addressing professional identity development and place within the care community. This study illustrates that a longitudinal clinician training program has the potential to influence professional identify development, particularly affect how clinicians view themselves as a resource in the HIV care community and begins to facilitate necessary connections to other clinicians and the wider care system.